Purification and Characterization of Escherichia coli MreB Protein - Nurse, Pearl (American Society for Biochemistry and Molecular Biology, 2013)
The actin homolog MreB is required in rod-shaped bacteria for maintenance of cell shape and is intimately connected to the holoenzyme that synthesizes the peptidoglycan layer. The protein has been reported variously to exist in helical loops under the cell surface, to rotate, and to move in patches in both directions around the cell surface. Studies of the Escherichia coli protein in vitro have been hampered by its tendency to aggregate. Here we report the purification and characterization of native E. coli MreB. The protein requires ATP hydrolysis for polymerization, forms bundles with a left-hand twist that can be as long as 4 μm, forms sheets in the presence of calcium, and has a critical concentration for polymerization of 1.5 μm.